F07 A frequency of concomitant disorders in presymptomatic huntington's disease patients. (September 2018) - Puch, Elżbieta Alicja; Witkowski, Grzegorz; Isalan, Mark; Mielcarek, Michał; Zielonka, Daniel
Abstract : There is growing evidence that Huntington's disease (HD) is a multi-system disorder. Although HD is predominantly recognized as a neurodegenerative disease, there is a mounting evidence that peripheral component to its pathology may also contribute to the disease progression. A number of pre-clinical studies in recent years revealed that murine models of HD develop a wide range of peripheral tissue abnormalities including eyes, cardiac and skeletal muscles, even at the pre-symptomatic stage. Hence, the aim of this study was to unravel concomitant disorders in the pre-symptomatic HD subjects. Our study was performed based on two EHDN Study sites in Poznan and Warsaw (Poland) and we collected data about: a frequency of concomitant disorders, age and number of CAG repeats from the REGISTRY and ENROLL-HD programs. In total, we identified 97 presymptomatic individuals using UHDRS as a criterion out of 542 patients between those two EHDN centers. The mean of age for the presymptomatic patients was 32.5 (±SD 8.9) years while the mean of the number of CAG repeats was 42.6 (±SD 3.1). We found that nearly a third of the group (28.9%) did not report any concomitant disorders. However, there was a number of patients that already developed psychiatric diseases (26.8%), predominantly depression was present in 18 cases. Moreover, we found the following comorbid conditions: musculoskeletal disorders and injuries (19.6%), allergies (18.6%), cardiovascular disorders (14.4%), neurological disorders (13.4%), gastrointestinal disorders (9.3%) and thyroid abnormalities (8.2%). A comparative analysis showed that the same comorbidities were observed in the symptomatic and presymptomatic HD subjects, only with a lower frequency in the latter. Our current study revealed for the first time that the peripheral component of HD pathology is already present in the group of presymptomatic HD patients at a similar level to the previously reported study on the group of symptomatic HD patients. The presence of concomitant disorders in over 70% presymptomatic patients might suggest an intrinsic role of mutated HTT across different human organs. These findings need further investigation in clinical settings, however they are in line with a number of preclinical studies that have previously identified a peripheral component in presymptomatic HD mouse models.